2018
DOI: 10.1038/s41564-018-0171-1
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of genomes from metagenomes via a dereplication, aggregation and scoring strategy

Abstract: Microbial communities are critical to ecosystem function. A key objective of metagenomic studies is to analyse organism-specific metabolic pathways and reconstruct community interaction networks. This requires accurate assignment of assembled genome fragments to genomes. Existing binning methods often fail to reconstruct a reasonable number of genomes and report many bins of low quality and completeness. Furthermore, the performance of existing algorithms varies between samples and biotopes. Here, we present a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
823
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 1,066 publications
(894 citation statements)
references
References 40 publications
2
823
0
1
Order By: Relevance
“…Reads were mapped to scaffolds with bowtie2 (Langmead and Salzberg, ) to determine their relative abundance. Automated binning was conducted with Metabat (Kang et al ., ) and Concoct (Alneberg et al ., ) using differential coverage information and the best genomic bins were selected with DAStool (Sieber et al ., ). Bins were imported into ggKbase (https://ggkbase.berkeley.edu) for further manual refinement based on their GC, coverage, taxonomy of scaffolds, as well as completion assessed according to the number of bacterial single copy genes present in each bin.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Reads were mapped to scaffolds with bowtie2 (Langmead and Salzberg, ) to determine their relative abundance. Automated binning was conducted with Metabat (Kang et al ., ) and Concoct (Alneberg et al ., ) using differential coverage information and the best genomic bins were selected with DAStool (Sieber et al ., ). Bins were imported into ggKbase (https://ggkbase.berkeley.edu) for further manual refinement based on their GC, coverage, taxonomy of scaffolds, as well as completion assessed according to the number of bacterial single copy genes present in each bin.…”
Section: Methodsmentioning
confidence: 97%
“…Reads were mapped to scaffolds with bowtie2 (Langmead and Salzberg, 2012) to determine their relative abundance. Automated binning was conducted with Metabat (Kang et al, 2015) and Concoct (Alneberg et al, 2014) using differential coverage information and the best genomic bins were selected with DAStool (Sieber et al, 2018). Bins were imported into ggKbase (https://ggkbase.berkeley.…”
Section: Genome Sequencing and Assemblymentioning
confidence: 99%
“…We have found that no single binning algorithm is the most effective for all 153 sample/environment types or even for all populations within one sample. The recently published method 154 DASTool tests a flexible number of different binning methods, evaluates all outcomes and chooses the best bin 155 for each population (Sieber et al 2018). A similar strategy has been utilized in a modular pipeline software 156 called MetaWRAP (Uritskiy et al 2018).…”
Section: Running Title: Curated and Complete Metagenome-assembled Genmentioning
confidence: 99%
“…The sequence mapping files were processed using SAMtools 1.6 (Li et al 2009 (Kang et al 2015). The four bin sets were supplied to DAS Tool 1.0 (Sieber et al 2018) for consensus binning to obtain the final bins. The quality of the genome bins was assessed through a single-copy marker gene analysis using CheckM 1.0.7 .…”
Section: Rasigraf Et Almentioning
confidence: 99%